Exploring climate adaptation in UAE residential communities: temperature trends, awareness, and technology adoption - Alkaabi, Khaula; Bouhaddioui, Chafik; Senghore, Salieu; Al Darmaki, Saif Obaid (Frontiers in Built Environment, 2025)
IntroductionThis study investigates how rising temperature trends influence climate adaptation behaviors in residential communities across the United Arab Emirates (UAE). It specifically examines the roles of community awareness, socio-economic status, and climate change perception in shaping household-level responses to heat stress and environmental variability.MethodsTemperature records from 1950 to 2100 were analyzed to capture long-term warming patterns and seasonal variability. A survey of 550 households was conducted to assess adaptation behaviors, with responses analyzed using Spearman’s rank correlation, linear regression, ANOVA, logistic regression, and multinomial logistic regression.ResultsFindings show significant long-term warming trends in the UAE. Survey data indicate that perceived heat discomfort negatively correlates with thermal comfort and strongly motivates technology adoption (ρ = −0.29, p < 0.001). Community awareness significantly predicts sustainable indoor and outdoor practices (p < 0.001). Higher income and education levels are associated with broader adoption of adaptation measures (p < 0.01). Climate change perception directly influences adaptation behaviors (p = 0.032), while health-related motivations substantially increase the likelihood of adopting technologies (Odds Ratio = 2.87, p < 0.05). Logistic regression further reveals that heat perception and energy cost concerns drive solar panel adoption, whereas sand and dust prevention measures improve residential comfort (p < 0.05).DiscussionThe results highlight the importance of socio-economic and perceptual factors in shaping adaptation strategies. Effective policy approaches should emphasize community awareness, inclusive planning, and targeted financial incentives to strengthen resilience in hot-arid residential contexts.